INSTRUCTIONAL DESIGN COLLABORATION OF LIBRARIANS IN THE SCHOOL LITERACY MOVEMENT - Johan, Riche Cynthia; Pramida, Deuis; Rohanah, Anah; Meidina, Inaya Shintia (Universitas Pendidikan Indonesia, 2018)
Conducting library learning activities in the classroom is one of the tasks and receivables in the Field Experience Practice (PPL) activities for all students of the Library of Education and Information Sciences University of Indonesia. Good practice research methodology is one of the alternative choices in estimating the steps that can be taken in the Field Experience Practice (PPL) program of students of the Library of Education and Information Sciences University of Indonesia, which will later become a product of collaboration between the school librarians and teachers at school, and can also present a school product design school learning product. Collaborating in the School Literacy Movement (GLS) activities is one of the bills that must be present in the program, wherein every student of the Library and Information Sciences University of Education program students is required to: 1) Be able to prepare the classroom learning collaboration design with coaching teachers, 2) Able to implement library learning practices, and 3) Able to describe Practical Review Results. Through the field experience (PPL) practice, the students of the Library of Education and Information Sciences University of Indonesia's Education program are able to obtain competencies relevant to their field in an optimal way to work in the workplace, especially in the field of school libraries.